2020
DOI: 10.1007/s12639-020-01288-4
|View full text |Cite
|
Sign up to set email alerts
|

Acquired antibody responses against merozoite surface protein-119 antigen during Plasmodium falciparum and P.vivax infections in South Indian city of Mangaluru

Abstract: Merozoite surface protein-1 (MSP-1) of malaria parasites has been extensively studied as a malaria vaccine candidate and the antibody response to this protein is an important indicator of protective immunity to malaria. Mangaluru city and its surrounding areas in southwestern India are endemic to malaria with Plasmodium vivax being the most widespread and prevalent species although P. falciparum also frequently infects. However, no information is available on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…The heterogeneity in the IgG OD values for PvMSP1 42 proteins was similar to that observed for the NBSA, which was irrespective of the parasite haplotype. Heterogeneity in IgG responses against PvMSP1 fragments and other molecules has been observed in previous studies [ 27 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 57%
“…The heterogeneity in the IgG OD values for PvMSP1 42 proteins was similar to that observed for the NBSA, which was irrespective of the parasite haplotype. Heterogeneity in IgG responses against PvMSP1 fragments and other molecules has been observed in previous studies [ 27 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 57%
“…Our selection of P. falciparum as an initial target was motivated by it being the most common malarial species in Palawan, Philippines (where several of us have been involved in malaria diagnosis and surveillance projects); a previous study found 74% of malaria infections arising in the region containing Palawan to arise from P. falciparum , while 18% arose from P. vivax . A comparison of the P. falciparum and P. vivax -specific antigens (Pf-MSP-1 19 and Pv-MSP-1 19 ) has demonstrated the ability to distinguish antibodies caused by infection with the two species, suggesting that our assay could be extended to create two variants of Cell 1, one expressing each of the species-specific antigens; we plan to pursue this in future work.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that while the Pv MSP-1 19 subunit is widely recognized and validated as one of the highly immunogenic parts of the protein ( Longley et al, 2020 ; Punnath et al, 2021 ), we have discovered through the SPOT-synthesis technique that other most reactive peptides do not align with this region. This outcome is likely due to the conformation-dependent nature of immunogenicity in this particular segment, as many studies use the recombinant expression of this subunit ( Cunha, Rodrigues & Soares, 2001 ; Bueno et al., 2008 ; Rocha et al, 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…Malarial infection elicits high antibody titers, mostly against the parasite’s blood stage, and those molecules persist even after treatment ( Braga, Fontes & Krettli, 1998 ; Morais et al, 2005 ; Costa et al, 2020 ). Individuals living in endemic areas for P. vivax swiftly develop considerable titers of antibodies towards specific parasite antigens ( Bueno et al, 2011 ; Fantin et al, 2021 ; França et al, 2021 ; Punnath et al, 2021 ; Tayipto et al, 2022 ). The identification of antibodies that target P. vivax antigens holds utility in delineating vivax malaria transmission regions, pinpointing asymptomatic reservoirs, predicting outbreaks, and facilitating the effective deployment of control measures, including prompt treatment ( Greenwood et al, 2008 ; Kim et al, 2014 ; Longley et al, 2017 ; O’Flaherty, Roe & Fowkes, 2022 ).…”
Section: Introductionmentioning
confidence: 99%